Pengaruh Inflasi Terhadap Minat Beli Konsumen Terhadap Produk - Suginam Suginam; Joli Afriany; Maringan Sianturi; Sri Rahayu (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Inflation is a condition where there is an increase in the price of goods and services continuously within a certain period of time. The impact of inflation is often in a negative direction due to increasing prices for products, causing a decrease in people's purchasing power, especially for people who have lower middle income levels. Assumptions or predictions of news related to inflation have already had an impact on the community. One of them is a decrease in consumer buying interest in goods. In this study, a research process will be carried out on the effect of inflation on consumer buying interest in a product, where the measurement is based on the positive or negative effect of inflation on consumer buying interest in the present. The research was conducted using quantitative methods by testing hypotheses. The results of the test show that the value of the inflation variable is 0.645 while the ttable value is 2.060, so it can be said that the hypothesis is rejected. In the sense that the effect of inflation does not have a negative impact on consumer buying interest in the product.